Residual kidney function after donor nephrectomy - Hamscho, N.; Wilhelm, A.; Döbert, N.; Menzel, C.; Gossmann, J.; Berner, U.; Zaplatnikov, K.; Scheuermann, E. H.; Grünwald, F. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: We evaluated the long-term residual renal function after donor nephrectomy using 99mTc-mercaptoacetyltriglycin (MAG3)-clearance. Donors, methods: Altogether 49 kidney donors were examined using 99mTc-MAG3-clearance after nephrectomy for donation to a relative (m:f = 11:38; age 55±27 years). The donors were examined 16±8 years postoperatively (1.5-26 years). 42 donors (86%) showed normal creatinine values, whereas the other seven (14%) exhibited slightly elevated levels. 20 donors were examined pre- and postoperatively and compared intraindividually. The kidney function was compared to the age adapted normal values of healthy persons with two kidneys (67–133% of age related mean). Results: After nephrectomy all donors showed a normal perfusion, good secretion, merely physiological intrarenal transit and a normal elimination from the kidneys. The 99mTc-MAG3-clearance was 69 ±15% of the normal mean value of healthy carriers of two kidneys regardless of the gender. 20 donors with a preoperative examination showed a significantly reduced total renal function from 84 ± 15% of the mean normal value preoperatively to 60 ± 15% postoperatively (p <0.0005). 15 donors of this group exhibited a significant functional increase of the residual kidney from 40% initially to 60% after nephrectomy (p = 0.003). No correlation was found between the initial 99mTc-MAG3-clearance measured prior to nephrectomy and the clearance levels after nephrectomy. Also, no correlation between the preoperative 99mTc- MAG3-clearance and the postoperative serum creatinine values could be observed. Altogether, 22% of the donors (11/49) developed arterial hypertension 10 ± 8 years after donation (1-23 years). This corresponds to the normal age prevalence of hypertension in the carriers of two kidneys. Three donors suffered from arterial hypertension prior to the operation. Conclusion: Kidney donors with normal or slightly elevated creatinine values postoperatively show a 99mTc- MAG3-clearance value of 69% of the mean value of healthy carriers of two kidneys. This may serve as a reference value for healthy carriers of one kidney. In our study we demonstrated a good compensation of the contralateral kidney via renal scintigraphy by means of 99mTc-MAG3-clearance.
Keywords: Kidney function; donor nephrectomy; 99mTc-MAG3-clearance